The phylogenetic relationships of Paramesotriton (Caudata: Salamandridae) based on partial mitochondrial DNA gene sequences - Gu, Xiaoming; Wang, Hui; Chen, Rongrong; Tian, Yingzhou; Li, Song (Zootaxa, 2012)
We examined phylogenetic relationships among newst of the genus Paramesotriton using partial mitochondrial gene se-quences, including the ND2-tRNATyr region (1415 bp) and the 12S rDNA-tRNAVal -16S rDNA region (1774 bp), from 42individuals of 10 recognized Paramesotriton species and outgroups by Bayesian inference (BI), Maximum likelihood(ML) and Maximum Parsimony (MP) methods. We found that, (1) Laotriton laoensis is the sister group of Paramesotri-ton, (2) the genus Paramesotriton is monophyletic, composed of either the P. caudopunctatus species group and the P.chinensis species group, or the subgenera Allomesotriton and Paramesotriton (3) P. longliensis and P. zhijinensis shouldbe placed in the P. caudopunctatus species group or subgenus Allomesotriton; (4) P. fuzhongensis is not a junior synonym of P. chinensis, and there is a close phylogenetic relationship between P. fuzhongensis and P. guangxiensis.